Mitochondrial connexin43 affects arrhythmogenesis with modulation of mitochondrial KATP channels. (25th November 2020) - Nishiyama, M; Someya, Y; Kumasaka, K; Satoh, W; Shindoh, C; Sato, H; Miura, M
Abstract: Introduction: Connexin43 (Cx43) forms gap junction channels in ventricular muscle and also exits in the inner mitochondrial membrane (mCx43). We have previously reported that carbenoxolone, a blocker of Cx43, increased the occurrence of arrhythmias with modulation of mitochondrial KATP channels (mKATP). Purpose: To examine how mCx43 and mKATP affect arrhythmogenesis, using cardiac-specific Cx43-deficient (Cx43−/−) mice. Methods: To generate cardiac-specific Cx43−/− mice, Cx43flox/flox mice were crossed with α-myosin heavy chain (Myh6)-cre+/− mice. The resulting offspring, Cx43flox/flox/ Myh6-cre+/− mice (Cx43−/− mice) and their littermates (Cx43+/+ mice), were used. Trabeculae were dissected from right ventricles of mouse hearts (length ∼0.9 mm, width ∼200 μm, thickness ∼80 μm). Force was measured with a strain gauge, and intracellular Ca2+ (Cai) with fura-2 and a CCD camera (22°C). To assess arrhythmogenesis, the minimal extracellular Ca2+ concentration (Caomin), at which arrhythmias were induced by electrical stimulation (0.3-s stimulus intervals, 100 nM isoproterenol), was determined in mouse trabeculae. Using isolated single ventricular myocytes, mitochondrial membrane potential (ΔΨm) was estimated with tetramethylrhodamine methylester (TMRM) fluorescence, ROS production was estimated with 2', 7'-dichlorofluorescein (DCF) fluorescence, and Ca2+ spark frequency was measured with fluo-4 and confocal microscopy. To investigate the roles of mKATP, 0.1 mM diazoxide, a mKATP channel opener, and 0.2 mM 5-hydroxydecanoic acid (5-HD), a mKATP channel inhibitor, were used. Results: Most of Cx43−/− mice suddenly died within 8 weeks (p<0.01). Cx43 was present in the inner mitochondrial membrane in Cx43+/+ mice, while it was not present in Cx43−/− mice. The resting and developed force and Cai transients by electrical stimulation (2-s stimulus intervals) showed no difference between Cx43−/− and Cx43+/+ mouse trabeculae (n=7). The Caomin in Cx43−/− mice was lower than that in Cx43+/+ mice (p<0.01), and diazoxide increased the Caomin in Cx43−/− mice (p<0.01), suggesting that arrhythmogenesis is increased in Cx43−/− mice and is decreased by diazoxide. Ca2+ spark frequency and DCF oxidation rate in Cx43−/− mice were higher than those in Cx43+/+ mice (p<0.01). They were decreased by diazoxide and were increased by 5-HD (p<0.01). TMRM fluorescence was decreased after electrical stimulation (1-s stimulus intervals) in Cx43−/− mice and was further decreased by 5-HD (p<0.01), suggesting depolarization of ΔΨm in Cx43−/− mice. Such decrease in TMRM fluorescence in Cx43−/− mice was suppressed by diazoxide and did not occur in Cx43+/+ mice. Conclusions: These results suggest that with modulation of mKATP, mCx43 plays important roles in ΔΨm determination, ROS production, and Ca2+ leak from the sarcoplasmic reticulum, thereby affecting arrhythmogenesis. Therefore, it is likely that mCx43 and mKATP could become a therapeutic target for controlling arrythmias. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Scientific Research (C) from Japan Society for the Promotion of Science